Greening Thy Neighbor: How the U.S. Inflation Reduction Act Drives Climate Finance Globally - te Kaat, Daniel Marcel; Raabe, Alexander; Tian, Yuanjie (The Review of Corporate Finance Studies, 2026)
Abstract Using granular data on global investment funds in difference-in-differences regressions around the announcement of the U.S. Inflation Reduction Act (IRA), we identify a novel international spillover channel of green industrial policies. Sustainable global investment funds received more inflows with the act announcement, in turn increasing their cross-border portfolio investments worldwide. Recipient economies better prepared to address climate change benefited most from sustainable global funds’ additional investments. Our results are stronger for funds with a larger portfolio share invested in the United States and in IRA-targeted industries. Yet, we see strong international spillovers even for non-U.S.-domiciled sustainable funds investing entirely outside the United States. Thus, global investment funds have become an important conduit for the international spillover of climate policies. (JEL F3, G1, G2, Q5)Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.